Development of Physics Providers Based on Arduino Uno Assisted With Infrared Sensors on Viscosity Materials - Suprianto; Rofah, Fila; Kamariyah, El Indahnia; Sumo, Maimon (Universitas Muhammadiyah Sidoarjo, 2025)
The aim of this research is to (1) produce an Arduino Uno-based physics teaching aid product with the help of an infrared sensor on viscosity materials, (2) to test the feasibility of the developed teaching aid, (3) to determine the practicality of the developed teaching aid, (4) to find out responses from students regarding the teaching aids developed. The model used in this development is the 4D development model of Definition (Define), Planning (Design), Development (Development) and Dissemination (Dissemination). The feasibility test was carried out by two material expert lecturers and two media expert lecturers, the feasibility test carried out by two material expert lecturers received a percentage score of 98% in the